IMPLEMENTATION OF PBL (PROBLEM BASED LEARNING) ON ANIMALS AROUND ME IN CLASS IIB SDN REJOSARI 01 - Anisa Nur Azizah; Kartinah; Mei Fita Asri Utari (STKIP Subang, 2023)
The aim of this study was to describe the implementation of PBL (Problem-Based Learning) in Learning Animals Around Me Class IIB at SDN Rejosari 01. The type of research used was descriptive qualitative research. The collection of data used is observation and documentation. The results of this study indicate that implementation of PBL (Problem-Based Learning) in Class IIB Animal learning around mein SDN Rejosari 01 helps increase the independence of students. Based on the learning outcomes obtained by students, it is explained that the implementation of PBL in this lesson can help students understand the existing material. The things that need to be improved in the implementation of PBL in learning Animals Around Me lie in the discussion activities carried out by students.